Longman prepararion courses for the TOEFL test : - Phillips, Deborah (Pearson Education, Inc, 2004)
Skills ' Strategies ' Confidence. This book/CD-ROM package gives students all the tools they need to succeed on the TOEFL(R) paper-based test. Providing both a comprehensive language skills course and a wealth of practice for all sections of the paper test, the Longman Preparation Course is appropriate for courses in TOEFL(R) test preparation or as a supplement to more general ESL courses.